Amiloride-sensitive cation channel 2 genotype affects the response to a carbon dioxide panic challenge. (October 2017) - Leibold, Nicole K; van den Hove, Daniel LA; Viechtbauer, Wolfgang; Kenis, Gunter; Goossens, Liesbet; Lange, Iris; Knuts, Inge; Smeets, Hubert J; Myin-Germeys, Inez; Steinbusch, Harry WM; Schruers, Koen RJ
Until recently, genetic research into panic disorder (PD) has had only limited success. Inspired by rodent research, demonstrating that the acid-sensing ion channel 1a (ASIC1a) is critically involved in the behavioral fear response to carbon dioxide (CO2 ) exposure, variants in the human homologue gene amiloride-sensitive cation channel 2 (ACCN2) were shown to be associated with PD. However, the relationship between changes in brain pH and ACCN2, as done in rodents by CO2 exposure, has not been investigated yet in humans. Here, we examined this link between the ACCN2 gene and the response to CO2 exposure in two studies: in healthy volunteers as well as PD patients and using both behavioral and physiological outcome measures. More specifically, 107 healthy volunteers and 183 PD patients underwent a 35% CO2 inhalation. Negative affect was assessed using visual analogue scales and the panic symptom list (PSL), and, in healthy volunteers, cardiovascular measurements. The single nucleotide polymorphism rs10875995 was significantly associated with a higher emotional response in PD patients and with an increase in systolic as well as diastolic blood pressure in healthy subjects. In all measurements, subjects homozygous for the T-allele showed a heightened reactivity to CO2 . Furthermore, a trend towards an rs685012 genotype effect on the emotional response was found in PD patients. We provide the first evidence that genetic variants in the ACCN2 are associated with differential sensitivity to CO2 in PD patients as well as healthy volunteers, further supporting ACCN2 as a promising candidate for future research to improve current treatment options.